2004
DOI: 10.1074/jbc.m407250200
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Caveolae/Lipid Rafts in the Uptake and Recycling of the Endogenous Cannabinoid Anandamide

Abstract: The mechanisms responsible for the uptake and cellular processing of the endogenous cannabinoid anandamide are not well understood. We propose that anandamide uptake may occur via a caveola/lipid raft-related endocytic process in RBL-2H3 cells. Inhibitors of caveola-related (clathrin-independent) endocytosis reduced anandamide transport by ϳ50% compared with the control. Fluorescein derived from fluorescently labeled anandamide colocalized with protein markers of caveolae at early time points following transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
146
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(158 citation statements)
references
References 44 publications
12
146
0
Order By: Relevance
“…Interestingly, it has been suggested that eCB uptake involves caveolae-related endocytosis (45), and caveolin-1, which is a marker for caveolae, displays properties similar to a fatty acid-binding protein (46). Because AEA-induced depression requires synaptic activity, but does not appear to require receptor or channel activation, it is possible that paired-pulse stimulation simply affects the physical state of the cell plasma membrane lipid bilayer in a way that modulates the transmembrane transport, which was previously reported for carrier-mediated transport of 5-hydroxytryptamine (47).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, it has been suggested that eCB uptake involves caveolae-related endocytosis (45), and caveolin-1, which is a marker for caveolae, displays properties similar to a fatty acid-binding protein (46). Because AEA-induced depression requires synaptic activity, but does not appear to require receptor or channel activation, it is possible that paired-pulse stimulation simply affects the physical state of the cell plasma membrane lipid bilayer in a way that modulates the transmembrane transport, which was previously reported for carrier-mediated transport of 5-hydroxytryptamine (47).…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism of CB1R internalization is not completely understood although recent findings suggest that both clathrin-coated pits and caveolae might be involved in this process [13]. In addition, it has been shown that the cellular accumulation of its ligand AEA is possibly due to caveolae-mediated endocytosis in RBL-2H3 cells [14] and that methyl-b-cyclodextrin (MCD), which extracts cholesterol from the plasma membrane, completely blocks AEA-induced cell death in a variety of cells, including PC12, C6, HEK and HL-60 cells [15]. All these data point towards an involvement of caveolae and of cholesterol-enriched membrane domains in the trafficking Abbreviations: AEA, anandamide; Cav1, caveolin 1; DRMs, detergent-resistant microdomains; MCD, methyl-b-cyclodextrin; GPCRs, G-protein-coupled receptors; TNE/TX-100, Tris Na EDTA/Triton X-100 buffer; PBS, phosphate buffer saline and function of CB1R.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, AEA is an uncharged lipid capable of traversing the bilayer unaided (10). Accordingly, several studies concluded that AEA uptake occurs by passive diffusion (10)(11)(12)(13)(14)(15), although facilitated diffusion and/or endocytosis have also been proposed (16)(17)(18)(19)(20).…”
mentioning
confidence: 99%